Fast High-Resolution S-PTHA Along the Western Mediterranean Sea Coastlines. Application to the Bay of Cannes - Souty , Viviane; Gailler, Audrey (Frontiers in Earth Science, 2021)
Probabilistic Tsunami Hazard Assessment (PTHA) is a fundamental framework for producing time-independent forecasts of tsunami hazards at the coast, taking into account local to distant tsunamigenic earthquake sources. If high resolution bathymetry and topography data at the shoreline are available, local tsunami inundation models can be computed to identify the highest risk areas and derive evidence-based evacuation plans to improve community safety. We propose a fast high-resolution Seismic-PTHA approach to estimate the tsunami hazard at a coastal level using the Bay of Cannes as test site. The S-PTHA process is firstly fastened by performing seismic and tsunami hazards separately to allow for quick updates, either from seismic rates by adding new earthquakes, or from tsunami hazard by adding new scenarios of tsunamis. Furthermore, significant tsunamis are selected on the basis of the extrapolation of a tsunami amplitude collected offshore from low-resolution simulations to an a priori amplitude nearshore using Green’s law. This allows a saving in computation time on high-resolution simulations of almost 85%. The S-PTHA performed in the Bay of Cannes exhibits maximum expected tsunami waves that do not exceed 1 m in a 2500-year period, except in some particular places such as the Old Port of Cannes. However, the probability to experience wave heights of 30 cm in this same period exceeds 50% along the main beach of Cannes and these results need to be considered in risk mitigation plans given the high touristic attraction of the area, especially in summer times.